Hubungan antara Komunikasi Keluarga dan Pencegahan Penyalahgunaan Narkoba Pada Siswa Kelas VIII SMPN 2 Rambah Samo Kabupaten Rokan Hulu Provinsi Riau - Defri Anita (Instructional Development Journal, 2018)
In writing this article the author chose a study entitled The Relationship Between Family Communication and Narcotics Abuse Prevention in Class VIII Students of SMPN 2 Rambah Samo, Rokan Hulu Regency, Riau Province.cThis study aims to describe the picture of family communication of students of SMPN 2 Rambah Samo, Rokan Hulu District, Riau Province; describe prevention of drug user students in Rambah Samo 2 Public High School, Rokan Hulu Regency, Riau Province; and knowing whether or not there is a relationship between family communication and prevention of drug abuse students at Rambah Samo 2 Middle School, Rokan Hulu District, Riau Province. This study addresses two variables, namely family communication and prevention of drug abuse. class VIII SMP 2 Rambah Samo Riau Province Rokan Hulu District Academic Year 2013/2014 which amounted to 143 students. then the sample used is 25% of the number of students, which is 25% x 143 = 36 students. The sampling technique used by researchers is a random sample. The type of research used in this study was post facto research or referred to after the fact. Data collection techniques used were documentation, observation, and questionnaires.The results showed that the quality of family communication was good, and prevention of drug abuse was also good. Thus, it can be stated that in general it is in a fairly good and good category. Based on the results of the calculation, it was found that the significance value was 0,000 which was smaller than the value of a = 0.05 and the calculated value was 0.371 in the "medium" category. The price coefficient is then tested for significance by comparing rtable to n = 80 at level 5%, then rtable = 0.220, where the value of r count> r table (0.371> 0.329) and the significance value obtained is less than 0.05. Thus, Ha is accepted namely there is a relationship between family communication and prevention of drug abuse students of the Middle School Rambah Samo 2, Rokan Hulu District, Riau Province. While the contribution of family communication and prevention of drug abuse amounted to 17.76%.